2015
DOI: 10.4049/jimmunol.1403243
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GM-CSF in T Cells Is Increased in Multiple Sclerosis and Suppressed by IFN-β Therapy

Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS). Studies in animal models of MS have shown that granulocyte-macrophage colony-stimulating factor (GM-CSF) produced by T cells is necessary for development of autoimmune CNS inflammation. This suggests that GM-CSF may have a pathogenic role in MS as well, and a clinical trial testing its blockade is ongoing. However, there have been few reports on GM-CSF production by T cells in MS. The objective of this study was to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 33 publications
7
142
1
1
Order By: Relevance
“…11 Some other studies have demonstrated high serum levels of IL-22 in MS during clinical relapses. Interleukin-22, along with IL-21 and IL-17, is considered part of the Th17 signature.…”
Section: Th1 Cells and Activated Cd8mentioning
confidence: 99%
“…11 Some other studies have demonstrated high serum levels of IL-22 in MS during clinical relapses. Interleukin-22, along with IL-21 and IL-17, is considered part of the Th17 signature.…”
Section: Th1 Cells and Activated Cd8mentioning
confidence: 99%
“…Consistent with this report, in our study, AxD astrocytes from patient iPSCs exhibited increased amounts of secreted GM-CSF, IL5, IL6, and TNFα. GM-CSF, IL6, and TNFα are well known as proinflammatory cytokines and are upregulated in various kinds of white matter diseases, including multiple sclerosis (MS) and neuromyelitis optica (NMO) [25][26][27][28]. IL-5 is a Th2 cell-type cytokine that is secreted by astrocytes and microglia [29], turning on the switch of inflammatory response by activating microglia to upregulate inflammatory response in the brain, cooperating with GM-CSF [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Outside of incidence, the frequency of GM-CSF-producing CD4 + in MS is also associated with disease severity [27]. IFN-β, a drug prescribed to control MS progression, may function in part through suppressing GM-CSF expression by peripheral blood T cells of MS patients [28]. Of note, however, there is a discrepancy in these reports as to whether the frequency of GM-CSF-producing CD8 + T cells was also elevated in MS patients [27,28].…”
Section: Th Cell-derived Gm-csf In Autoimmune Neuronal Diseasementioning
confidence: 99%
“…IFN-β, a drug prescribed to control MS progression, may function in part through suppressing GM-CSF expression by peripheral blood T cells of MS patients [28]. Of note, however, there is a discrepancy in these reports as to whether the frequency of GM-CSF-producing CD8 + T cells was also elevated in MS patients [27,28]. Nevertheless, it is likely that CD4 + T cell-derived GM-CSF plays a pivotal role in the pathogenesis of MS and might be a promising target for therapeutic intervention.…”
Section: Th Cell-derived Gm-csf In Autoimmune Neuronal Diseasementioning
confidence: 99%